1998
DOI: 10.1093/hmg/7.3.507
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum and genotype-phenotype analyses in Cowden disease and Bannayan-Zonana syndrome, two hamartoma syndromes with germline PTEN mutation

Abstract: The tumour suppressor gene PTEN, which maps to 10q23.3 and encodes a 403 amino acid dual specificity phosphatase (protein tyrosine phosphatase; PTPase), was shown recently to play a broad role in human malignancy. Somatic PTEN deletions and mutations were observed in sporadic breast, brain, prostate and kidney cancer cell lines and in several primary tumours such as endometrial carcinomas, malignant melanoma Human Molecular Genetics, 1998, Vol. 7, No. 3 508 and thyroid tumours. In addition, PTEN was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
425
2
15

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(459 citation statements)
references
References 31 publications
14
425
2
15
Order By: Relevance
“…These results are in keeping with findings that heterozygous PTEN/MMAC1ϩ/Ϫ animals display hyperplastic and dysplastic lesions in many organs in the absence of PTEN/MMAC1 mutations of the remaining allele (27). Studies in humans with Cowden syndrome, who carry heterozygote PTEN/MMAC1 germline mutations, have also shown that in a number of cases, the tumors do not have detectable PTEN/MMAC1 locus LOH (28), indicating that somatic deletion of the wild-type allele has not occurred. Similarly, heterozygous loss of PTEN/ MMAC1 in mouse thyroid and prostate leads to an increase in the proliferative indices of these tissues, again raising the possibility that heterozygous loss alone of PTEN/MMAC1 may play a role in tumor development and progression (27).…”
Section: Discussionsupporting
confidence: 87%
“…These results are in keeping with findings that heterozygous PTEN/MMAC1ϩ/Ϫ animals display hyperplastic and dysplastic lesions in many organs in the absence of PTEN/MMAC1 mutations of the remaining allele (27). Studies in humans with Cowden syndrome, who carry heterozygote PTEN/MMAC1 germline mutations, have also shown that in a number of cases, the tumors do not have detectable PTEN/MMAC1 locus LOH (28), indicating that somatic deletion of the wild-type allele has not occurred. Similarly, heterozygous loss of PTEN/ MMAC1 in mouse thyroid and prostate leads to an increase in the proliferative indices of these tissues, again raising the possibility that heterozygous loss alone of PTEN/MMAC1 may play a role in tumor development and progression (27).…”
Section: Discussionsupporting
confidence: 87%
“…32,33 Although definitive studies are lacking in breast cancer, that this may occur in humans is suggested by the fact that heterozygous inactivation of PTEN results in 3 dominantly inherited disorders: Cowden syndrome (associated with a predisposition to thyroid and breast cancers), Bannayan-Zonana syndrome and Lhermitte-Duclos syndrome. [3][4][5] Of course, this more likely suggests that it is easier to mutate the second allele once the first allele is lost.…”
Section: Resultsmentioning
confidence: 99%
“…2 Germline mutations have been reported in Cowden syndrome and Bannayan-Zonana syndrome, 2 dominantly inherited conditions causing predisposition to a variety of cancers including breast cancer. [3][4][5] Homozygous somatic mutations have also been recorded in a high percentage of human tumors, common among which are glioblastoma multiforme 6 -8 and endometrial cancer. 9 -11 Genetic, functional and animal modeling studies have substantiated the tumor-suppressor function of PTEN.…”
Section: Pten (Mmac1/tep1mentioning
confidence: 99%
“…1994. and more recently with Cowden disease and a aermline mutation in the tumour suppressor gene PTEN (Marsh et al 1998). …”
Section: Patients and Methods Data Sourcesmentioning
confidence: 99%